(untitled) (International Journal of Engineering and Computer Science, 2015)
Message authentication is one of the most effective ways to thwart unauthorized and corrupted messages from being forwarded in wireless sensor networks (WSNs). For this reason, many key management techniques have been developed for message authentication, based on either symmetric-key cryptosystems or public-key cryptosystems. Most of the authentication schemes have the limitations of security, in addition to lack of scalability and resilience to node compromise attacks. To address these issues, a polynomial-based scheme was recently introduced. The polynomial schemes have the weekness to build in threshold value determined by the degree of the polynomial. In the proposed system, a scalable authentication scheme is SAMA based Modified Elgamal Signature (MES). It enabling intermediate nodes authentication and allows any node to transmit an unlimited number of messages without suffering the threshold problem. In addition this scheme can also provide message source privacy